Developing English Vocabulary Module as Learning Media for Applied English for Communication - Gusti Ayu Putu Diah Permata Sari AR; Ketut Yuniati; I Gusti Agung Ngurah Agung Yudha Pramiswara; I Nyoman Ariyoga; I Komang Agus Widiantara; Putu Wiraningsih (Faculty of Letters Universitas Balikpapan, 2023)
This research aims to develop an effective English vocabulary module as a learning media for the Applied English for Communication course. The study applied Research and Development (RnD) model using the ADDIE design. The module consists of six topics with relevant vocabulary exercises. Besides, the module was validated by subject matter experts and media experts, who rated it with an average score of 4.7. A questionnaire was also distributed to the students and overall average score of 0.85, indicating high acceptance of the module among the students. Additionally, the effectiveness of the module was assessed through pre-test and post-test evaluations. The researcher also conducted tests for normality, homogeneity, and significance using SPSS version 16. The normality test resulted in values of 0.39 for the pre-test phase and 0.12 for the post-test phase, indicating normal distribution of the data. The homogeneity test yielded a significance value of 0.468, indicating group homogeneity. The significance test showed a value of 0.000, indicating a significant difference between the pre-test and post-test scores. Thus, it can be concluded that the developed English vocabulary module is an effective learning media for the Applied English for Communication course in the Hindus’ Communication Studies program-STAHN Mpu Kuturan Singaraja.